Laminar Free Convection in Three Dimensional Inclined Porous Annulus with Fins on the Inner Cylinder - M. AL-Mashaat, Saad; H. AL-Hafidh, Manal (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
An experimental and numerical study was carried out to investigate the heat transfer by natural convection in a three dimensional annulus enclosure filled with porous media (silica sand) between two inclined concentric cylinders with (and without) annular fins attached to the inner cylinder under steady state condition. The experiments were carried out for a range of modified Rayleigh number (0.2 ≤Ra*≤ 11) and extended to Ra*=500 for numerical study and for annulus inclination angle of (δ = 0˚, 30˚, 60˚ and 90˚). The numerical study was to give the governing equation under assumptions that used Darcy law and Boussinesq’s approximation and then it was solved numerically using finite difference approximation. It was found that the average Nusselt number depends on (Ra*, Hf, δ and Rr ). The results showed that the increasing of the fin length increases the heat transfer rate for any fin pitch unless the area of the inner cylinder exceeds that of the outer one; then the heat will be stored in the porous media. A comparison was made between the results of the present work and those of other researches for the case without fins and excellent agreement was obtained.